Determine the equation of g(x) that results from translating the function f(x)=(x+6)^2 to the right 9 units

To translate

f(x) = (x + 6)^2 to the right by 9 units

subtract 9 from (x + 6)

So, g(x) = (x + 6 - 9)^2

g(x) = (x - 3)^2

Image contains plot of f(x) and g(x).

Graph.png

ANSWER: g(x) = (x - 3)^2

Thank You !

:)

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up